Ergonomics Analysis of Computer Use in Distance Learning during the Pandemic of COVID-19 - Anindya Apriliyanti Pravitasari; Mulya Nurmasnsyah Ardisasmita; Fajar Indrayatna; Intan Nurma Yulita (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
One impact of the COVID-19 pandemic on education is the mandated learning from home or distance learning (DL) in both state and private education institutions to prevent the transmission of COVID-19. DL may require long periods of time in front of a computer screen, which can create ergonomic issues such as eye, shoulder or neck problems, low back pain, and fatigue or stress. This study was structured to look at the ergonomic behavior of students in the statistics department at Padjadjaran University. The data were gathered using questionnaire, and there were 146 respondents who were willing to answer and send back the questionnaire. The results of the analysis show that the majority of students do not have knowledge about ergonomics when using computers. However, students agree that wrong posture can affect health conditions, especially those related to musculoskeletal disorders. The real impact felt by students is the health condition around their neck, shoulders, waist, bottoms, and wrists.